Kecerdasan Buatan dan Kearifan Lokal: Menegosiasikan Nilai-Nilai Budaya Madura dalam Pendidikan Islam Berorientasi Masa Depan - Achmad Muchlis; Mohammad Akhwan Muchlis; Mohammad Muchlis Solichin; Misnawi Misnawi; Achmad Muzammil Alfan Nasrullah (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2026)
The rapid development of artificial intelligence (AI) in education presents challenges for Islamic education within local cultural contexts, particularly regarding how data-driven technologies can be adopted without diminishing the moral values and local epistemic structures that support the social legitimacy of Islamic education. This conceptual paper examines this issue through the context of Madura, an Indonesian island society whose Islamic education system is closely connected to local wisdom through pesantren traditions, the epistemic authority of kyai, communal practices such as kompolan, and moral values expressed in bâburughân beccè'. Through a qualitative synthesis of recent studies on Madurese local wisdom and AI integration in Islamic education, this paper develops a conceptual framework that views AI and local wisdom as a negotiation space. Three key aspects require careful management: knowledge authority, character development and moderation, and access and equity. The paper argues that future-oriented Islamic education in Madura should implement a value-based AI adoption model with teachers acting as mediators, ensuring that technology strengthens rather than replaces the relational and communal dimensions of pesantren pedagogy.